2022
DOI: 10.3390/gels8020088
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Biological Features of Cactus Coated Bacterial Cellulose Hydrogels

Abstract: The current study was aimed at developing BC-Cactus (BCC) composite hydrogels with impressive mechanical features for their potential applications in medical and environmental sectors. BCC composites hydrogels were developed through cactus gel coating on a never dried BC matrix. The FE-SEM micrographs confirmed the saturation of BC fibrils with cactus gel. Additionally, the presence of various functional groups and alteration in crystalline behavior was confirmed through FTIR and XRD analysis. Mechanical testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…A total of 3% of the absorption peaks in the 3%COS+C+Z+S group were weak, while the 3%COS+Z+S, 3%COS+C+S, and 3%COS+C+Z groups were enhanced sequentially due to the bending vibration of the double bond over the single bond −COO and C=O in the amide group and N-H in the amide group to different degrees. When two different metal ions form a binary cross-linker, the gel film may form a unique structure different from the single ion cross-linker, due to the coexistence of the two cross-linking mechanisms and the different degrees of stretching vibrations generated by the absorption summit [21]. The above showed that −COO − and −NH 3 + interacted with metal ions, confirming the generation of double-network gel films.…”
Section: Ftir Analysismentioning
confidence: 85%
“…A total of 3% of the absorption peaks in the 3%COS+C+Z+S group were weak, while the 3%COS+Z+S, 3%COS+C+S, and 3%COS+C+Z groups were enhanced sequentially due to the bending vibration of the double bond over the single bond −COO and C=O in the amide group and N-H in the amide group to different degrees. When two different metal ions form a binary cross-linker, the gel film may form a unique structure different from the single ion cross-linker, due to the coexistence of the two cross-linking mechanisms and the different degrees of stretching vibrations generated by the absorption summit [21]. The above showed that −COO − and −NH 3 + interacted with metal ions, confirming the generation of double-network gel films.…”
Section: Ftir Analysismentioning
confidence: 85%
“…Some researchers have modified BC by changing its surface charge using carboxyl groups [8]. Hyaluronic acid-BC composites, chitosan-BC composites, cactus/BC hydrogels and metallic nanoparticles combined with BC have also been obtained by numerous researchers to improve the biological properties of BC [9][10][11]. Moreover, researchers have reported that BC composites with pullulan, chitosan, cactus and acrylic acid hydrogels increase the healing rate of burn wounds and may be used as wound dressing composites [11][12][13][14][15].…”
mentioning
confidence: 99%